Toward a social research perspective in Colombian multicultural language classrooms - Garzón Duarte, Eliana (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This essay is the result of a deep and critical reading of recent studies on the socio-linguistic field.It discusses how to address the roles of identity, agency and investment from a research perspective in Colombian multicultural language classrooms. The rationale presented here may serve as a foundation for foreign language teachers who face the necessity of reformulating their objectives and instructional procedures to integrate the language learner and the language learning context taking into account the multiculturalism of our country.